Global Transcriptome Analyses Reveal Differentially Expressed Genes of Six Organs and Putative Genes Involved in (Iso)flavonoid Biosynthesis in Belamcanda chinensis - Tian, Mei; Zhang, Xiang; Zhu, Yan; Xie, Guoyong; Qin, Minjian (Frontiers in Plant Science, 2018)
Belamcanda chinensis (L.) DC., a perennial herb of the family Iridaceae, is rich in a variety of (iso)flavonoids with significant organ-specific distribution and has a swollen rhizome that is widely used in East Asia as a traditional medicine. In the present study, comprehensive transcriptomes of six organs (root, rhizome, aerial stem, leaf, flower, and young fruit) of B. chinensis were obtained by high-throughput RNA-sequencing and de novo assembly. A total of 423,661 unigenes (mean length = 618 bp, median length = 391 bp) were assembled and annotated in seven databases: Non-redundant protein sequences, Nucleotide sequences, Swiss-Prot, Protein family database, euKaryotic Ortholog Groups, Kyoto Encyclopedia of Genes and Genomes (KEGG), and Gene Ontology (GO). A total of 4995 transcription factors were identified, including 408 MYB, 182 bHLH, 277 AP2/ERF, and 228 WRKY genes. A total of 129 cytochrome P450 unigenes belonging to 10 divergent clans were identified and grouped into clades in a phylogenetic tree that showed their inferred evolutionary relationship. Differentially expressed unigenes among the six organs were subjected to GO and KEGG enrichment analysis to profile the functions of each organ. Unigenes associated with (iso)flavonoid biosynthesis were then profiled by expression level analysis. Additionally, the complete coding sequences of six predicted enzymes essential to the (iso)flavonoid pathway were obtained, based on the annotated unigenes. This work reveals clear differences in expression patterns of genes among the six organs and will provide a sound platform to understand the (iso)flavonoid pathways in B. chinensis.